2019
DOI: 10.1080/00140139.2019.1629638
|View full text |Cite
|
Sign up to set email alerts
|

Wearing body armour and backpack loads increase the likelihood of expiratory flow limitation and respiratory muscle fatigue during marching

Abstract: The effect of load carriage on pulmonary function was investigated during a treadmill march of increasing intensity. 24 male infantry soldiers marched on six occasions wearing either: no load, 15 kg, 30 kg, 40 kg or 50 kg. Each loaded configuration included body armour which was worn as battle-fit or loose-fit (40 kg only). FVC and FEV 1 were reduced by 6 to 15% with load. Maximal mouth pressures were reduced post load carriage by up to 11% (inspiratory) and 17% (expiratory). Increased ventilatory demands asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 39 publications
2
36
0
Order By: Relevance
“…The finding of no change in ΔP imax is in agreement with existing studies (Griffiths and McConnell, 2007;Faghy and Brown, 2015;Lomax et al, 2018;Faghy and Brown, 2019). Lomax et al (2019) found that ΔP imax was not correlated with changes in 100 or 200 m swim times showing that increases in P imax did not determine the magnitude of improvement in performance. Unchanged RMF could be due to potential ineffective training, however in the present study, P imax was increased in EXP when compared to pre-intervention values which was not apparent in CON, indicating training was effective in increasing absolute strength.…”
Section: Respiratory Muscle Fatiguesupporting
confidence: 91%
See 2 more Smart Citations
“…The finding of no change in ΔP imax is in agreement with existing studies (Griffiths and McConnell, 2007;Faghy and Brown, 2015;Lomax et al, 2018;Faghy and Brown, 2019). Lomax et al (2019) found that ΔP imax was not correlated with changes in 100 or 200 m swim times showing that increases in P imax did not determine the magnitude of improvement in performance. Unchanged RMF could be due to potential ineffective training, however in the present study, P imax was increased in EXP when compared to pre-intervention values which was not apparent in CON, indicating training was effective in increasing absolute strength.…”
Section: Respiratory Muscle Fatiguesupporting
confidence: 91%
“…Nevertheless, reductions in FVC (seen both in hypoxia and at reduced ambient temperatures) causes reductions in the volume of air the lungs can support. This increases work of breathing, reduces lung compliance and may lead to RMF (Armstrong et al, 2019). In the present study, the additive effect of both hypoxia and a cold ambient temperature likely led to reduction in FVC and thus P imax .…”
Section: Respiratory Muscle Fatiguementioning
confidence: 53%
See 1 more Smart Citation
“…The primary goal of BT is to transform civilians into soldiers. As such, the BT programme is necessarily arduous, involving cyclic high impact loading activities and tasks such as up and downhill running, foot-drill, circuit training, strength training, and marching with external loads of up to 40 kg (Armstrong et al 2019;Chapman et al 2019). Similar cyclic high impact activities involving continuous locomotion and rapid changes in direction are associated with exerciseinduced breast pain in athletic populations, through excessive and repetitive movement in the vertical, medial, and lateral directions (Burbage and Cameron 2017;Mason, Page, and Fallon 1999;White, Scurr, and Smith 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In the poststroke rehabilitation process, monitoring of muscle activity is very important to know the developments of muscle strength. Nicola CD Armstrong et al 18 investigated the effect of load carriage on pulmonary function during a treadmill march of increasing intensity. The results of muscle fatigue using surface electromyogram (sEMG) for rehabilitation training system were reported by Liu et al 19 Jannatul Naeem et al 20 proposed the mechanomyography-based muscle fatigue detection during electrically elicited cycling in patients with spinal cord injury; it could be implemented in functional electrical stimulation systems to increase patient safety and to optimize patient training.…”
Section: Introductionmentioning
confidence: 99%